Soberania em tempos democráticos: François Guizot e Alexis de Tocqueville - Oliveira, Vítor Castro de (2012)
The main objective of this dissertation is to conduct a comparative analysis of the works of François Guizot and Alexis de Tocqueville. This work is inserted, therefore, in a conjunct of studies which, especially from the 1980s on, attempts to evaluate the intellectual debt of Tocqueville towards Guizot. It is known that both of them lived in an era marked by political instability and devoted themselves to discern the political and social meaning of the French Revolution, attempting to comprehend the new relations between individuals and the State. Initially, what will be researched is the influence of the concept of civilization that Guizot elaborated by the end of the 1820s over the historic view of Tocqueville, particularly over what the latter called “democratic revolution”. The analysis must demonstrate that the authors had a fundamentally different evaluation of the effects of the social transformations France had been through. Supporting different appraisals of the society in which they lived, they judged in distinct ways the relations of this society with the political power. Posteriorly, it will be researched the role reserved to the citizens on the construction of the political order, since both rejected the idea that sovereignty belonged uniquely to the royalty. Indeed, avoiding to attribute the political power to any individual or social group, they evoked alternately the sovereignty of reason or of the human gender and sought different manners of applying these ideas to the exercise of power. However, neither systematized their reflections about the subject in a great work of political theory. Their ideas are dispersed in their history books and texts of political intervention, so as the contextual dimension is an obligatory element of this work, which attempts to comprehend the ambiguities of the authors and the transformations in their conceptual formulations, relating them to specific political problems they faced.